1994
DOI: 10.1063/1.868221
|View full text |Cite
|
Sign up to set email alerts
|

Rates of thermal relaxation in direct simulation Monte Carlo methods

Abstract: For internal energy relaxation in rarefied gas mixtures, exact relationships are derived between the selection probability P employed in direct simulation Monte Carlo (DSMC) methods and the macroscopic relaxation rates dictated by collision number Z in Jeans’ equation. These expressions apply to the Borgnakke–Larsen model for internal energy exchange mechanics and are not limited to the assumption of constant Z. Although Jeans’ equation leads to adiabatic relaxation curves, which coalesce to a single solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 19 publications
0
77
0
Order By: Relevance
“…Rotational and vibrational energy exchange was performed using the BorgnakkeLarsen method. 10 Following Haas et al, 19 multiple relaxation events were prohibited. The methodology for selecting relaxing particles was that of Gimelshein et al 20 For simplicity, constant relaxation probabilities of 0.30 and 0.01 for rotation and vibration, respectively, were used.…”
Section: Strong Shock In Dissociating Nitrogenmentioning
confidence: 99%
“…Rotational and vibrational energy exchange was performed using the BorgnakkeLarsen method. 10 Following Haas et al, 19 multiple relaxation events were prohibited. The methodology for selecting relaxing particles was that of Gimelshein et al 20 For simplicity, constant relaxation probabilities of 0.30 and 0.01 for rotation and vibration, respectively, were used.…”
Section: Strong Shock In Dissociating Nitrogenmentioning
confidence: 99%
“…In Ref. 30, relaxation probabilities for both the particle selection and pair selection are discussed in detail. In the baseline DSMC calculations to be discussed here, the Z V cont of Millikan and White 31 is used.…”
Section: Review Of Energy Exchange Models For Hypersonic Flowsmentioning
confidence: 99%
“…21 Table VI summarizes the values of Z R ϱ , T R * , and v for N 2 , O 2 , and NO that are used in the DSMC calculations. In addition, the temperature-dependent collision numbers of Haas et al 30 were used. Figure 5 shows a comparison of the collision numbers predicted by the original MW ͑Refs.…”
Section: B Investigation Of Energy Exchange Modelsmentioning
confidence: 99%
“…The number density remains constant in time @n=@t ¼ 0. The relaxation rates of the kinetic model equations have been compared numerically with the corresponding ones of the DSMC method and it has been found that good agreement is observed by setting [34,14].…”
Section: Appendix a Relaxation Rates In A Homogenous Gasmentioning
confidence: 89%